2020
DOI: 10.1038/s41598-020-69015-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of desmoplastic small round cell tumors identifies actionable therapeutic targets: a report from the Children’s Oncology Group

Abstract: to further understand the molecular pathogenesis of desmoplastic small round cell tumor (DSRct), a fatal malignancy occurring primarily in adolescent/young adult males, we used next-generation RNA sequencing to investigate the gene expression profiles intrinsic to this disease. RNA from DSRCT specimens obtained from the Children's Oncology Group was sequenced using the Illumina HiSeq 2000 system and subjected to bioinformatic analyses. Validation and functional studies included WT1 ChIP-seq, EWS-WT1 knockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 34 publications
3
50
0
Order By: Relevance
“…We next performed immunohistochemistry on paraffin-embedded DSRCT cell line xenografts or cell pellets (SK-DSRCT1) to confirm the presence of WT1 using an antibody raised to the C-terminus of WT1, and to explore expression of EGFR and phosphorylated EGFR, given that this ERBB RTK was the most consistently activated in cell lines and tumors tested. Strong nuclear staining for the WT1 C-terminus was detected in all samples probed, most likely representing EWSR1-WT1 in these novel DSRCT models, as a recent transcriptome profiling study of has confirmed a lack of native WT1 transcripts in DSRCT (35). EGFR was detected at varying levels in the different DSRCT patient xenografts or xenografted DSRCT cell lines.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…We next performed immunohistochemistry on paraffin-embedded DSRCT cell line xenografts or cell pellets (SK-DSRCT1) to confirm the presence of WT1 using an antibody raised to the C-terminus of WT1, and to explore expression of EGFR and phosphorylated EGFR, given that this ERBB RTK was the most consistently activated in cell lines and tumors tested. Strong nuclear staining for the WT1 C-terminus was detected in all samples probed, most likely representing EWSR1-WT1 in these novel DSRCT models, as a recent transcriptome profiling study of has confirmed a lack of native WT1 transcripts in DSRCT (35). EGFR was detected at varying levels in the different DSRCT patient xenografts or xenografted DSRCT cell lines.…”
Section: Resultsmentioning
confidence: 66%
“…Western blotting with the C-terminal WT1 antisera confirmed the presence of WT1 in all of the new DSRCT cell lines ( Figure 3D ). The band detected is most likely EWS-WT1 as transcriptomic analysis has shown that the JN-DSRCT-1 cell line does not express wildtype WT1 (35).…”
Section: Resultsmentioning
confidence: 99%
“…Silencing EWS-WT1 causes proliferation loss, growth arrest and gene expression analysis indicates a repression of estrogen signaling and highlight therapeutic genetic vulnerabilities, such as FGFR4, JAK3, mTOR, PDGF, ERG, and TGFB1 genes [12]. Another study that evaluated potential therapeutic targets performed RNA sequencing of 12 tumor samples from pediatric patients with DSRCT found high expression of IGF2, FGFR4, CD200 and CD276, the latter two molecules are candidates for immune checkpoint inhibitor therapy [75] In terms of therapy, the first use of JN-DSRCT-1 cells was to test de effect of rapamycin induced in inducing apoptotic death [76]. The mechanism involves the up-regulation of Bax concomitant Bcl-xL down-regulation.…”
Section: Current and Emerging Therapy For Relapsed Or Progressive Dismentioning
confidence: 99%
“…gene promoter, providing the basis to test the activity of anti-IGF-1R antibodies in the metastatic setting [119]. Also, IGF2 has been up-regulated by the fusion product and is a potential target [75].…”
Section: Targeting C-met and Insulin Growth Factor Pathwaymentioning
confidence: 99%
See 1 more Smart Citation